Pengaruh Motivasi dan Lingkungan Kerja terhadap Kepuasan Kerja Pegawai pada PT. KB Bank Tbk Jakarta - Eva Oktafianingsih; Suharini Suharini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The development of human resources within a company is an effort to enhance the quality of human resources aimed at improving the quality of workers. Every company hopes and strives to advance by implementing various structured methods in education, training, and development programs to enhance employee performance. The purpose of this research is to determine the influence of motivation and work environment on employee job satisfaction at PT. KB Bank Tbk Jakarta. The data collection method in this study was conducted by distributing questionnaires to 70 respondents who are employees of PT. KB Bank Tbk Jakarta. The method used is a quantitative method with a saturated sampling technique. The data utilized consists of primary and secondary data. The results of this study indicate that motivation and work environment have a positive and significant impact on job satisfaction.